2007
DOI: 10.1897/06-555
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Toxicity of Pesticide Formulations (Atrazine, Chlorpyrifos, Permethrin) to Glochidia and Juveniles of Lampsilis siliquoidea

Abstract: Freshwater mussels are among the most imperiled faunal groups in North America; approximately 67% of the nearly 300 native freshwater mussel species (family Unionidae) are listed as endangered, threatened, or of special concern. Despite evidence that glochidia and juvenile life stages are highly sensitive to some chemical contaminants, the effects of pesticides on early life stages of unionid mussels are largely unknown. In the United States, pesticide registration is based on toxicity data of the active ingre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 22 publications
(32 reference statements)
0
23
0
Order By: Relevance
“…Toxicity endpoints for mussels include 24-h larval (glochidia) survival, 96-h juvenile survival, and 28-d juvenile survival, length, weight, and biomass. Water-only toxicity testing has demonstrated that juvenile mussels are sensitive to a variety of contaminants associated with sediment including metals and ammonia, but may be less sensitive to organic contaminants compared with commonly tested species [8][9][10][11][12][13]. Moreover, juvenile mussels are in direct contact with sediment, often burrowing into the upper 1-cm to 2-cm layer of sediment [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicity endpoints for mussels include 24-h larval (glochidia) survival, 96-h juvenile survival, and 28-d juvenile survival, length, weight, and biomass. Water-only toxicity testing has demonstrated that juvenile mussels are sensitive to a variety of contaminants associated with sediment including metals and ammonia, but may be less sensitive to organic contaminants compared with commonly tested species [8][9][10][11][12][13]. Moreover, juvenile mussels are in direct contact with sediment, often burrowing into the upper 1-cm to 2-cm layer of sediment [14].…”
Section: Introductionmentioning
confidence: 99%
“…Lampsilis siliquoidea was selected for testing because this species of mussel has been cultured and tested routinely in water-only toxicity tests, has been demonstrated to be sensitive to contaminants typically of concern in sediment, and exhibits a sensitivity similar to that of other freshwater mussels [9][10][11][12][13]. The sediment was collected from the East Branch of the Grand Calumet River (located south of Lake Michigan, USA, and contained elevated concentrations of metals and organic compounds).…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies was undertaken to refine methods for conducting acute and chronic toxicity tests with early life stages of mussels [6][7][8][9][10]. Based on these studies and previous literature, the American Society for Testing and Materials (ASTM) recently published a standard guide for conducting laboratory toxicity tests with freshwater mussels [11].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the objectives of the present study were to evaluate the acute toxicity of copper, ammonia, or chlorine to glochidia and juvenile mussels and compare the sensitivity of early life stages of freshwater mussels with commonly tested cladoceran, amphipod, and fish species. Other toxicants, such as pesticides, were evaluated in two of the companion papers [7,8]. Companion papers in this issue evaluate intra-and interlaboratory variability in acute toxicity tests with freshwater mussels [9] and evaluate the chronic toxicity of copper or ammonia to early life stages of mussels [10].…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies were undertaken to refine methods for conducting acute and chronic toxicity tests with early life stages of mussels [3,7,[13][14][15]. Based on these studies and previous literature, American Society for Testing and Materials (ASTM) recently published an international Standard Guide For Conducting Laboratory Toxicity Tests With Freshwater Mussels [16].…”
Section: Introductionmentioning
confidence: 99%